Comparative effectiveness research for prostate cancer radiation therapy: current status and future directions. (January 2012) - Shen, Xinglei; Zaorsky, Nicholas G; Mishra, Mark V; Foley, Kathleen A; Hyslop, Terry; Hegarty, Sarah; Pizzi, Laura T; Dicker, Adam P; Showalter, Timothy N
Comparative effectiveness research aims to help clinicians, patients and policymakers make informed treatment decisions under real-world conditions. Prostate cancer patients have multiple treatment options, including active surveillance, androgen deprivation therapy, surgery and multiple modalities of radiation therapy. Technological innovations in radiation therapy for prostate cancer have been rapidly adopted into clinical practice despite relatively limited evidence for effectiveness showing the benefit for one modality over another. Comparative effectiveness research has become an essential component of prostate cancer research to help define the benefits, risks and effectiveness of the different radiation therapy modalities currently in use for prostate cancer treatment.